The Effect of Gembili Yogurt (Dioscorea esculenta L.) Intake on Lipid Profile of Hypercholesterolemic Rats - Erika Oktavia Rahmasari; Rosida (Universitas Dr Soetomo, 2023)
Hypercholesterolemia is a condition in which the concentration of cholesterol in the blood exceeds the normal value. Yogurt is food product that has been shown to lower blood. The addition of inulin can support the cholesterol-lowering effect of yogurt. Gembili (Dioscorea esculenta L.) is a high inulin food ingredient. This study aims to determine the effect of giving gembili yogurt (D. esculenta L.) on the lipid profile (total cholesterol, LDL, and triglyceride) of hypercholesterolemic rats. The study was conducted on 30 male hypercholesterolemic Wistar rats which were grouped using a simple randomized system into 1 control group and 4 intervention groups. Subjects were given 1, 2, 3, and 4 ml/day of gembili yogurt for 14 days. Total cholesterol, and LDL were determined using the CHOD-PAP method and triglyceride level was determined using the GPO-PAP method. Giving gembili yogurt with doses of 1, 2, 3, and 4 ml/day within 2 weeks could significantly reduce lipid profile on hypercholesterolemic rats, the largest decrease was occurred at group with a dose of 4 ml yoghurt/day with total cholesterol levels of 100.68 mg/dl, LDL levels 28.87, and triglyceride levels 85.80 mg/dl